Impact of participative leadership on employee innovation behaviour in multinational enterprises - Gjorgjina Gina Sherovska (Mednarodno Inovativno Poslovanje)
Examining the behaviour of organizational leaders across all levels is essential for the organization's growth. In the context of multinational organizations, the purpose of this research is to examine the connection between participatory leadership and innovative employee behaviour as well as the moderating role of workplace culture in this relationship. 96 employees and their immediate supervisors from different industries were asked to participate in this study which were employed by multinational corporations via filling a questionnaire. SPSS was utilized to answer the research question and investigate the interactions. Despite the dominant autocratic management style in the North Macedonian business sector, leadership is considered a major asset in today's ever-changing environment. The findings suggest, when institutional complexity is high, it may be more difficult to adopt a participatory approach due to a greater gap between leaders and those below them. This study provides new insight into the existing literature on the topic. One of the practical contributions provided by this research is the examining how participatory leadership affects employees' creative behaviour and the moderating role of workplace culture in this relationship, the study also aims to offer new knowledge to the corpus of existing research, as well as to contribute to the knowledge of leadership and innovative employee behaviour in MNEs.